2019
DOI: 10.1177/0954408919878984
|View full text |Cite
|
Sign up to set email alerts
|

Quadratic multiple regression model and spectral relaxation approach to analyse stagnation point nanofluid flow with second-order slip

Abstract: The present paper is concerned to study the influence of second-order slip, mixed convection, viscous and Joule dissipations, thermophoretic and Brownian diffusions on steady stagnation point nanofluid flow over a stretching sheet embedded in a porous medium with passive control of nanoparticles. Graphs for velocity, temperature and concentration of present nanofluid flow model, obtained by using spectral relaxation method, are discussed in detail for various parameters. Apart from it, present results are veri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Now for conversion of system of PDEs into ODEs we need similarity transformations. For current system we use following transformations 49 given by …”
Section: Interpreting the Flow Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Now for conversion of system of PDEs into ODEs we need similarity transformations. For current system we use following transformations 49 given by …”
Section: Interpreting the Flow Analysismentioning
confidence: 99%
“…Khan et al 48 investigated the nanoliquid flowing via an extendable surface under the effect of boundary layer approximation. Kumar et al 49 implemented the spectral relaxation way to find the solution of nanoliquid flowing via a slippery plate. Gangadhar et al 50 achieved the numerical solution of Casson liquid accompanied with convection phenomenon over sheet having nonlinear phenomenon with the benefit of spectral relaxation approach.…”
Section: Introductionmentioning
confidence: 99%
“…Sahoo and Nandkeolyar [30] studied Casson hydromagnetic fluid flow under Joule's law of heating and viscous dissipation effects and observed that in the presence of viscous and Joule dissipation, the Casson parameter has the propensity to decay temperature. Kumar et al [31] analyzed the nanofluid flow with Joule's heating and viscous dissipation effects and found that the occurrence of Eckert number enhances the thermophoretic and Brownian diffusion effects.…”
Section: Introductionmentioning
confidence: 99%
“…This is the reason why nanoliquids are used very frequently in locomotive industry and in aerospace engineering. Kumar et al 5 discussed the stagnation point flow of nanoliquids over a perpendicular sheet with 2nd order velocity slip. They concluded that an increase in Brownian motion of nanoparticles tends to dilute the concentration of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%